Sharpe Gallery : James Albertson - Roberto Barni - Erwin Bohatsch - Francesco Bonami - Lorenzo Bonechi - Mark Dean - Peter Drake - Arthur Gonzalez - Jane Irish - Cheryl Laemmle - Michael Lucero - Mark McCloud - Michael Ottersen - Thomas Schindler - Mark Strathy. (New York : Sharpe Gallery, 1985)
James Albertson - Roberto Barni - Erwin Bohatsch - Francesco Bonami - Lorenzo Bonechi - Mark Dean - Peter Drake - Arthur Gonzalez - Jane Irish - Cheryl Laemmle - Michael Lucero - Mark McCloud - Michael Ottersen - Thomas Schindler - Mark Strathy
Sharpe Gallery : James Albertson - Roberto Barni - Erwin Bohatsch - Francesco Bonami - Lorenzo Bonechi - Mark Dean - Peter Drake - Arthur Gonzalez - Jane Irish - Cheryl Laemmle - Michael Lucero - Mark McCloud - Michael Ottersen - Thomas Schindler - Mark Strathy, Sharpe Gallery, New York, 1985
boek